Effects of Polymeric Formula vs Elemental Formula in Neonatal Piglets With Short Bowel Syndrome. (May 2014) - Hua, Zheng; Turner, Justine M.; Mager, Diana R.; Sigalet, David L.; Wizzard, Pamela R.; Nation, Patrick N.; Ball, Ron O.; Pencharz, Paul B.; Wales, Paul W.
Background : Intestinal adaptation is important for recovery in short bowel syndrome (SBS). This process is dependent on the presence of enteral nutrition (EN) and trophic factors, such as glucagon-like peptide-2 (GLP-2). In clinical practice, elemental formula is often used to feed neonates with SBS, whereas animal studies suggest polymeric formula promotes better intestinal adaptation. In neonatal piglet models of SBS, with or without ileum, we compared the elemental with the polymeric formula, including the effect on endogenous GLP-2. Materials and Methods : Forty-eight piglets underwent 75% mid-intestinal resection with jejunoileal anastomosis, 75% distal-intestinal resection with jejunocolic anastomosis (JC), or sham without resection. Parenteral nutrition (PN) started postoperatively, tapering as EN was increased, according to clinical criteria, based on diarrhea and weight. Within groups, piglets were randomized to an isocaloric/isonitrogenous elemental (amino acid) or polymeric (intact protein) diet. Plasma GLP-2 and histology for adaptation were measured at 14 days. Results : Within both SBS and control groups, no difference in adaptation was observed according to diet. A difference was observed only within the JC piglet group with regard to clinical outcomes. In these piglets, compared with elemental formula, the polymeric formula was associated with more diarrhea ( P = .023) and longer duration of PN support ( P = .047). Conclusion : An overall benefit of the polymeric formula over the elemental formula on gut adaptation was not observed. Furthermore, SBS piglets without ileum had less ability to tolerate polymeric formula, contributing to more days of PN support.